Galactooligosaccharides as a protective agent for intestinal barrier and its regulatory functions for intestinal microbiota. (May 2022) - Wang, Geng; Wang, Haidong; Jin, Yuyue; Xiao, Zhiping; Umar Yaqoob, Muhammad; Lin, Yueying; Chen, Haohan; Wang, Minqi
Graphical abstract: Highlights: The GOS improved the intestinal morphology and protein levels of tight junction. The GOS alleviated the inflammatory response in NF-κB dependent way. The GOS enhanced the secretion of mucin and SIgA in small intestine. The GOS promoted the formation of a predominant flora of probiotics. Abstract: Present study was conducted to comprehensively investigate the protective effects of galactooligosaccharides (GOS, 100%) against LPS-induced intestinal barrier damages, and the regulatory effect for intestinal microbes. Results showed that GOS intervention restored villi (jejunum and ileum) integrity, which were atrophic and broken in LPS-challenged mice. Electron microscopy, western blotting and immunofluorescence analysis exhibited that mice administrated with GOS showed higher expression of tight junction, which was confirmed in IPEC-J2 cells model. Meanwhile, the GOS increased the secretion of mucin and SIgA, as well as it alleviated inflammatory response caused by LPS in NF-κB dependent way. Administration of GOS could also increase the relative abundances of several specific friendly bacteria, and enhance the adaptability of intestinal microbiota. Collectively, these results indicated the potential of GOS for protecting intestine from injuries caused by stress as LPS challenge.